'I was not able to go there': Introducing a skills perspective about how tourists navigate in Los Angeles. (September 2019) - Lucas, Leopold
This article argues that considering individuals' skills is fundamental in explaining tourists' practices. Navigation here is conceptualized as one of the spatial stakes that individuals must address when they inhabit a city. From this question, this article emphasizes the fact that coping with space should not be taken for granted but requires skills that relate to individuals' own levels of experience in terms of the practices of places. To this end, this article first engages in a theoretical discussion of Goffman, Ingold and Wittgenstein's ideas. Then, at the empirical level, importance is given to tourists' experiences, as they describe their ways of coping with space. Through an original mapping of their itineraries in Los Angeles, we examine tourists' justification process concerning their 'régimes d'action'.